Power, Blame, and the Female Body: A Critical Discourse Study of Melanie Martinez’s “Strawberry Shortcake” - Hassan, Amelia; Lasut, Fadilah Adelina; Nani, Nur Afriyanti; Hulamahe, Rahayu A.; Dako, Rahman Taufiqrianto; Katili, Adriansyah Abu (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
Language shapes social meanings and contributes to the construction of gendered power relations. This study examines how Melanie Martinez’s “Strawberry Shortcake” constructs, negotiates, and challenges patriarchal ideology through a Critical Discourse Analysis framework. Addressing a gap in existing research, which rarely explores how a single pop song intertwines critiques of body shaming and the blaming of female victims, the study analyzes the lyrics using Fairclough’s three-dimensional model. The analysis demonstrates how the culinary metaphors of “icing on top” and “strawberry shortcake” function simultaneously as markers of objectification and as ironic vehicles for feminist resistance. Patterned repetition such as “It’s my fault” is shown to strategically deconstruct the logic of victim-blaming, while interdiscursive references to purity norms reveal the contradictory expectations imposed on girls and women. Beyond identifying these linguistic patterns, the findings illustrate how the song repositions the female voice from an objectified figure toward an assertive agent who critiques socialized entitlement and misplaced responsibility. This study contributes to CDA scholarship by showing how popular music can serve as a site of ideological transformation and offers an analytical model that supports critical media literacy, particularly in recognizing subtle gendered messages in contemporary cultural texts.